ESKALASI KETERAMPILAN MEMBACA DENGAN METODE BERCERITA - Zakaria; utami maulida utami (Jurnal Gentala Pendidikan Dasar, 2021)
This study aims to analyze extensively the concept of reading skills of elementary school students using the storytelling method. This research is a qualitative descriptive research with content analysis method (content analysis). The storytelling method is a way that can develop the reading skills of elementary school students. The storytelling method has interesting techniques so that teachers can apply the storytelling method to students and develop reading skills. This research is useful as an explication of the storytelling method to develop the reading skills of students who do not yet have an interest in reading or are even classified as unable to read. The storytelling method conveyed has been adapted to the times and adapted to the millennial generation